IMPROVING THE METHODOLOGY FOR USING 3D GRAPHICS SOFTWARE IN THE TRAINING OF TECHNOLOGY TEACHERS - Musurmonkulov Qilichbek Orolovich (Web of Journals Publishing, 2024)
In the process of training students of Technology Science, 3-dimensional graphics programs (3D graphics programs) play an important role. This article will bring ways to improve the methodology for using 3D graphics programs. In the educational process, the advantages and pedagogical effectiveness of the application of these programs are analyzed.
Keywords: Software, 3d graphics, pedogogical practice, theory of constructive education, visualization, pedagogical technologies, methodology.